Specific Microbial Communities Are Selected in Minimally-Processed Fruit and Vegetables according to the Type of Product - Giuseppina Sequino; Vincenzo Valentino; Elena Torrieri; Francesca De Filippis (Foods, 2022)
Fruits and vegetables (F&V) products are recommended for the daily diet due to their low caloric content, high amount of vitamins, minerals and fiber. Furthermore, these foods are a source of various phytochemical compounds, such as polyphenols, flavonoids and sterols, exerting antioxidant activity. Despite the benefits derived from eating raw F&V, the quality and safety of these products may represent a source of concern, since they can be quickly spoiled and have a very short shelf-life. Moreover, they may be a vehicle of pathogenic microorganisms. This study aims to evaluate the bacterial and fungal populations in F&V products (i.e., iceberg lettuces, arugula, spinaches, fennels, tomatoes and pears) by using culture-dependent microbiological analysis and high-throughput sequencing (HTS), in order to decipher the microbial populations that characterize minimally-processed F&V. Our results show that F&V harbor diverse and product-specific bacterial and fungal communities, with vegetables leaf morphology and type of edible fraction of fruits exerting the highest influence. In addition, we observed that several alterative (e.g., Pseudomonas and Aspergillus) and potentially pathogenic taxa (such as Staphylococcus and Cladosporium) are present, thus emphasizing the need for novel product-specific strategies to control the microbial composition of F&V and extend their shelf-life.